(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
Analysis of the Celtiberian standards or signa equitum. We discuss the different types and its evolution from the simplest models, forked with the ends rolled like a scroll, to the most complex ones, finished in symmetric human heads or horse protomes, clearly related to the celtiberian ‘rider and horse fibulae‘. We analyze its relationship with equestrian aristocratic elites and its possible evolution from Iberian models.